2016
DOI: 10.1038/cddis.2016.359
|View full text |Cite
|
Sign up to set email alerts
|

A novel crosstalk between CCAR2 and AKT pathway in the regulation of cancer cell proliferation

Abstract: Human CCAR2 has recently emerged as having a pivotal role in the DNA damage response, promoting apoptosis and repair of heterochromatic DNA breaks. However, less is known about the function of CCAR2 in tumor formation and cancer progression. Here, we demonstrate, for the first time, that CCAR2 loss inhibits the proliferation of cancer cells, but preserves the growth of normal cells. Investigating the mechanisms responsible for this differential effect, we found that CCAR2 depletion specifically impairs the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Importantly, CCAR2 is a core component of the DBIRD complex, a multiprotein complex, which acts at the interface between core messenger RNP particles and RNA polymerase II, and integrates transcript elongation with regulation of alternative splicing [34]. CCAR2 depletion could affect the anchorage-independent growth of several types of cancer cells [35]. Taking these data into account, and on the basis of our present data, we hypothesize that CCAR2, which is present at high levels even in ESRP1-negative cells such as COLO320DM, can perform its multiplicity of function, independent of ESRP1.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CCAR2 is a core component of the DBIRD complex, a multiprotein complex, which acts at the interface between core messenger RNP particles and RNA polymerase II, and integrates transcript elongation with regulation of alternative splicing [34]. CCAR2 depletion could affect the anchorage-independent growth of several types of cancer cells [35]. Taking these data into account, and on the basis of our present data, we hypothesize that CCAR2, which is present at high levels even in ESRP1-negative cells such as COLO320DM, can perform its multiplicity of function, independent of ESRP1.…”
Section: Discussionmentioning
confidence: 99%
“…CCAR2, a widely expressed protein, is required for cell proliferation and is associated with poor prognosis in squamous cell carcinoma [52]. CCAR2 silencing decreases cell proliferation by altering the AKT pathway [53]. Two studies have indicated that CCAR2 interacts with HSP60 and survivin to form a CCAR2-HSP60-survivin complex in mitochondria.…”
Section: Interaction Between Hsp60 and Survivin In Mitochondriamentioning
confidence: 99%
“…LKB1 negatively regulates AKT1 via DBC1 and TRB3. DBC1 is known to act as a positive regulator of AKT1 S473 phosphorylation via Tribbles3 (TRB3) (11). It does so by transcriptional repression of TRB3 expression.…”
Section: Pyst Induces Energy Deficit and Activates Lkb1-ampk Pathway:mentioning
confidence: 99%
“…Activated LKB1, through an unknown mechanism, leads to the degradation of DBC1 protein. DBC1 is a transcriptional co-repressor for TRB3 expression (11). In the absence of growth factors, Tribbles3 is known to sequester AKT1 and prevent its phosphorylation and activation by upstream kinases (11,12).…”
Section: Energy Deficit Is Critical For the Induction Of Mitotic Arrementioning
confidence: 99%
See 1 more Smart Citation